Initial clinical experiences of the muscle-preserving double door cervical laminoplasty with adjustable mini plates - Wu, Wenliang; Zhang, Shuai; Yan, Tingbin (Frontiers in Surgery, 2023)
Shirashi’s double door laminoplasty method was a popular decompression procedure for cervical myelopathy. In this paper, we introduced a modified double door laminoplasty based on Shirashi’s method with preliminary results. This study retrospectively analyzed 22 patients who underwent modified double door laminoplasty. During procedure, a single segment of the unilateral lamina was separated from the cervical semispinalis muscle and the multifidus muscle space for the preparation of lamina groove. A self-developed mini titanium plate was used to fix the inner side of the spinous process to complete the fixation after open-door process. The VAS, JOA scores and QoL scale were recorded for pain assessment, neurological and functional recovery. The overall curvature and range of motion of C2-C7 were measured with X-ray images. Changes in sagittal diameter of spinal canal were measured by CT scans. MRI was used to measure the cross-sectional area of cervical paravertebral muscles. All 22 patients successfully recovered with this procedure. The mean operation time, blood loss and follow-up durations were 117 ± 25 minutes, 149±32 ml and 16.1 ± 3.6 months respectively. The preoperative, 3-month postoperative and 12-month postoperative JOA scores were 9.35±3.25, 13.74±4.86 and 15.73 ± 5.19 respectively. with improvement rates of 57.4% and 83.4%. Mean VAS scores before, 3 months after and 12 months after surgery were 1.81 ± 0.79, 2.82 ± 1.56 and 2.18 ± 1.34 respectively. The C2-7 lordotic angle and overall range of motion shows no statistical difference preoperatively and 12 post-surgery. The average sagittal diameter of the cervical spinal canal was enlarged from 9.15±1.55mm to 14.25±1.46mm. The average area of cervical paravertebral volume measured preoperatively and 3 months post operation was 84% of pre-operative value respectively. This value was improved to 93% of the preoperative value at 12 months post-surgery. This paper introduced initial experience on a modified posterior cervical double-door laminoplasty that was based on Shirashi's method, featuring creating bilateral laminar grooves on both sides and fixing central gap with self-developed mini plates. This procedure prevented obvious axial symptoms and improved patients’ quality of life, which provided a baseline for further research with larger cohorts.